Tools and principles for microbial gene circuit engineering. - Bradley,RW; Buck,M; Wang,B (Journal of Molecular Biology, 2015)
Synthetic biologists aim to construct novel genetic circuits with useful applications through rational design and forward engineering. Given the complexity of signal processing that occurs in natural biological systems, engineered microbes have the potential to perform a wide range of desirable tasks that require sophisticated computation and control. Realising this goal will require accurate predictive design of complex synthetic gene circuits and accompanying large sets of quality modular and orthogonal genetic parts. Here we present a current overview of the versatile components and tools available for engineering gene circuits in microbes, including recently developed RNA-based tools that possess large dynamic ranges and can be easily programmed. We introduce design principles that enable robust and scalable circuit performance such as insulating a gene circuit against unwanted interactions with its context, and we describe efficient strategies for rapidly identifying and correcting causes of failure and fine-tuning circuit characteristics.